HUBUNGAN KEJADIAN ANEMIA PADA IBU HAMIL DENGAN BERAT BADAN LAHIR RENDAH DI RSUD RA BASOENI MOJOKERTO - SUSANTI, IKA YUNI (HOSPITAL MAJAPAHIT (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT), 2016)
Anemia in pregnant women due to blood thinning occurs more pronounced with increasing age of the pregnancy so that the frequency increases. Anemia during pregnancy causes fetal growth is less than optimal impact on the occurrence of low birth-weight babies. The purpose of this study was to analyze the relationship between the incidence of anemia and low birth weight babies in hospitals RA Basoeni Mojokerto. This study uses a case control design. The population in the study were all women deliver in hospitals RA. Basoeni Mojokerto during January to December 2014, as many as 281 respondents, while samples were selected using simple random sampling as many as 56 people. The results showed that pregnant women who are anemic in hospitals RA. Basoeni Mojokerto there are 28 respondents (50%). Respondents in this study most of having a baby of low birth weight by 24 (42.85%). Based on Chi-Square test can be concluded that there is a relationship of anemia in pregnant women with low birth weight babies in hospitals RA.Basoeni Mojokerto year 2014.Oleh pregnant women because it is attentive to the needs / nutrition during pregnancy to the fullest and always meriksakan her pregnancy at least 4 times the health worker or the nearest healthcare.Keyword: anemia, low birth weight, pregnancy